Challenges of Heritage Buildings in Mitigating Mosquito Breeding and Urban Flooding Risks: The Case of George Town, Penang, Malaysia (Architecture Image Studies, 2025)
George Town, the capital of the Malaysian state of Penang, is a city steeped in rich history and diverse cultures, which have influenced its unique architectural styles and tantalising cuisine over the centuries. It is widely recognised as Malaysia's gastronomical capital; its vibrant streets overflowing with an array of delectable street food are destinations for a feast for the senses. The preservation of these cultures has earned the city, along with Malacca, the prestigious designation of a UNESCO World Heritage Site in 2008, making it a must-visit destination for any traveller to immerse themselves in the beauty and diversity of Malaysia's rich heritage. Because of its unique heritage, the site faces new challenges. The article sheds light on potential threats of mosquito breeding in historical structures in urban areas, which could be elevated by occurrences of water-related disasters. This article also discusses the challenges faced by built environment professionals in providing structural mitigations for flood disasters and the inflexibilities in altering the existing infrastructures and heritage buildings to reduce the risk of mosquito breeding and urban flash floods.  The current condition could pose a health hazard for local residents as well as visitors from around the globe, as they may be exposed to diseases like dengue. The article underlines the significance of risk communication and delves into the measures taken by municipal authorities for mitigation and disaster risk reduction as well as the prevention of mosquito breeding in the heritage sites.